Are passwords finally dying?. Issue 2 (February 2016) - Everett, Cath
Abstract : People have been talking about the death of the password for years. In fact, Microsoft founder Bill Gates first declared its imminent extinction at the RSA Security Conference in 2004 as, he attested, it was simply unable to "meet the challenge" of keeping critical information secure. The seemingly endless security breaches of 2015 have once again led to a flurry of speculation over the imminent demise of the key offender, the password. Possible alternatives such as biometrics have proven too costly and complex to implement to take off in the corporate space. Moreover, it seems that passwords are being given a new lease of life by technology such as password vaults and by their inclusion in two-factor authentication solutions that are growing steadily in popularity, explains Cath Everett.